Effects of culture condition towards fatty acids in a harpacticoid copepod; Amphiascoides neglectus (Lang, 1965) - Kassim, Zaleha (ConferenceSeries.com, 2016)
Copepods have been found as one of the best live feed in aquaculture. This study was carried out to determine the development time, growth performance and fatty acid content of a marine copepod, Amphiascoides neglectus, potentially become live feed for marine larval rearing. The laboratory experiments were designed to expose the population of A. neglectus to different sets of temperature, pH and salinity treatment. The copepods were maintained in the combination of salinity of 15, 25 and 35ppt, pH of 5,7,9 and temperature of 25, 28,35oC for 25days under hygienic condition. Fatty acid content was determined using gas chromatography method. The life cycle consists of six naupliar stages, five copepodite stages and an adult stage. Total development time of each life stages was from 9±3.61 h to 17 ±2.65 h and range from 53.86 µm to 593.98 µm in size. Nauplii, copepodites and adult stage showed highest population density when cultured in 28oC, salinity 25ppt and pH9 (T28P9S25). The bad growth performance was shown when they were cultured in 35oC, salinity 15 and pH5 (T35P5S15). A.neglectus cultured in T28P9S25 demonstrated the highest fatty acid contents with linoleic acid C18:2n-6 (LA), eicosapentaenoic acid C20:5n-3 (EPA), docosahexaenoic acid C22:6n-3 (DHA), arachidonic acid C20:4n-6 (ARA) and linolenic acid C18:3n-3 (LNA). The finding of this study could become the baseline for the optimum culture condition of A.neglectus